Subhepatic appendicitis in a 27-year-old male: a case report from Odahulle General Hospital of Ethiopia - Abagojam, Abduletif Haji Ababor; Dekema, Remedan Jemal; Woyimo, Tamirat Godebo; Mohammed, Jafer Yasin; Tukeni, Kedir Negesso (Frontiers in Gastroenterology, 2025)
The appendix is a small, tube-shaped organ that connects to the cecum, the beginning of the large intestine. Though its role is unknown, it can become infected, resulting in acute appendicitis, which, if not detected and treated early, can lead to serious consequences. Though the symptoms and signs of acute appendicitis are straightforward in most cases, atypical locations might result in unexpected presentations, which can lead to complications as it might not be detected and treated early. This case report describes a 27-year-old Black Ethiopian male patient who presented with right upper abdominal pain, low-grade fever, palpitations, and diarrhea. He also had some episodes of vomiting of ingested matter. Upon physical examination, the patient appeared acutely sick with some degree of tachycardia. An abdominal examination revealed right upper abdominal quadrant tenderness, though there was no palpable mass noted. Laboratory investigations were unremarkable apart from the stool examinations which revealed many pus and red blood cells and was full of actively motile bacteria. An abdominal ultrasound showed an enlarged subhepatic appendix with an internal fecalith 1 cm in depth, that was partially compressible, with no obvious peri appendiceal free fluid or other pathology. An assessment of subhepatic acute appendicitis was suspected and an emergency operation was conducted which revealed an inflamed subhepatic appendix that was on the verge of rupture. At a subsequent follow-up, the patient had significantly improved as evidenced by the lack of symptoms including abdominal pain, fever, and palpitation. Subhepatic appendix is a rare condition caused by either the non-descent of the cecum or intestinal malrotation during early development. As its presentation is not classical and hence mimics other pathologies, the diagnosis may be overlooked, resulting in perforation and abscess formation and leading to increased morbidity and possibly mortality. A high level of suspicion is required for early diagnosis and treatment to improve patient outcomes.